A CTAB-modified S/C nanocomposite cathode for high performance Li–S batteries. Issue 95 (28th September 2016) - Wang, Xiuzhen; Qin, Sai; Sun, Pingping; Sun, Yueming; Xu, Qingyu; Lai, Changwei; Fan, Qi
Abstract : Two unique S/C/Ni foam nanostructure electrodes are fabricated by a facile cetyltrimethyl ammonium bromide (CTAB) modified electrodeposition method. Abstract : Two unique S/C/Ni foam nanostructure electrodes are fabricated by a facile cetyltrimethyl ammonium bromide (CTAB) modified electrodeposition method. With this strategy, S nanodots and carbon nanocomposites (carbon nanotube (CNT) or reduced graphene oxide (RGO)) are directly deposited onto the Ni foams, which obviously increase the S loading and electron/ion conductivity of the whole electrodes. Ascribed to the unique structure, the hybrid electrodes exhibit balanced high performance, including: large reversible capacity, stable cyclability and high coulombic efficiency. Among them, the S/RGO/Ni foam nanostructure electrode exhibits better performance, with a high reversible capacity of 1421 mA h g −1 initially and over 790 mA h g −1 after 500 cycles with a very low capacity degradation rate of less than 0.09% per cycle and high coulombic efficiency of 98% at a high-rate of 0.5C.